Effects of breaking up prolonged sitting via exercise snacks intervention on the body composition and plasma metabolomics of sedentary obese adults: a randomized controlled trial - Jianming Zhou; Xiaoning Gao; Dandan Zhang; Chuanwu Jiang; Wenbing Yu (Endocrine Journal)
Obesity resulting from long-term sedentary a significant threat to human health. This study explores the effects of exercise snack intervention on body composition and plasma metabolomics in sedentary obese adults. Participants in the snack group were subjected to 4 days of sprint exercises by stair-climbing per week for 12 weeks. Systemic and regional fat mass, epicardial adipose tissue (EAT), abdominal visceral (AVFA) and subcutaneous (ASFA) fat area and plasma metabolomics data were measured before and after intervention. A higher improvement of EAT, AVFA and ASFA in the snack group compared to that in the control group, with a significant interaction effect (p < 0.05). The key differential metabolites between the two groups include isoleucine, glycine and serine. The proposed exercise snack effectively reduced the amount of AVFA and EAT. The change in body composition may be associated with the altered pathways of isoleucine, glycine, and serine metabolism.